Famine food of vegetal origin consumed in the Netherlands during World War II - Tom Vorstenbosch; Ingrid de Zwarte; Leni Duistermaat; Tinde van Andel (BMC, 2017)
Abstract Background Periods of extreme food shortages during war force people to eat food that they normally do not consider edible. The last time that countries in Western Europe experienced severe scarcities was during World War II. The so-called Dutch famine or Hunger Winter (1944-1945) made at least 25,000 victims. The Dutch government took action by opening soup kitchens and providing information on wild plants and other famine food sources in "wartime cookbooks." The Dutch wartime diet has never been examined from an ethnobotanical perspective. Methods We interviewed 78 elderly Dutch citizens to verify what they remembered of the consumption of vegetal and fungal famine food during World War II by them and their close surroundings. We asked whether they experienced any adverse effects from consuming famine food plants and how they knew they were edible. We identified plant species mentioned during interviews by their local Dutch names and illustrated field guides and floras. We hypothesized that people living in rural areas consumed more wild species than urban people. A Welch t test was performed to verify whether the number of wild and cultivated species differed between urban and rural citizens. Results A total number of 38 emergency food species (14 cultivated and 21 wild plants, three wild fungi) were mentioned during interviews. Sugar beets, tulip bulbs, and potato peels were most frequently consumed. Regularly eaten wild species were common nettle, blackberry, and beechnuts. Almost one third of our interviewees explicitly described to have experienced extreme hunger during the war. People from rural areas listed significantly more wild species than urban people. The number of cultivated species consumed by both groups was similar. Negative effects were limited to sore throats and stomachache from the consumption of sugar beets and tulip bulbs. Knowledge on the edibility of famine food was obtained largely by oral transmission; few people remembered the written recipes in wartime cookbooks. Conclusion This research shows that 71 years after the Second World War, knowledge on famine food species, once crucial for people's survival, is still present in the Dutch society. The information on famine food sources supplied by several institutions was not distributed widely. For the necessary revival of famine food knowledge during the 1940s, people needed to consult a small group of elders. Presumed toxicity was a major reason given by our participants to explain why they did not collect wild plants or mushrooms during the war.